Frs 2 application of black & scholes meron’s (bsm) model on Malaysian capital market - Samsuddin, Mas Ervina; Haron, Rosmawati; Jasni, Nur Syuhada (2011)
Purpose - To examine the validity of Black & Scholes Meron's (BSM) formula to value executive stock options (ESOs) on 100 largest companies in Malaysia and compare the market value of 100 companies with the BSM model values. Design/methodology/approach - The sample is obtained by companies that were listed on the Main Board of Bursa Malaysia in 2005. Top 100 companies was based on total assets are taken as sample in this research for a period of three years, 2003 until 2005 according to sectors. This study use BSM formula for analysis of stock options valuation and to examine whether the model used may lead to overestimation of ESOs expenses. Findings - The results revealed that there is serious price differential compared to the standard BSM model for the three year period. The standard BSM model clearly overstates the value of share options which should be expensed by companies. The market values of share options are clearly below the values predicted by the standard BSM model. Therefore, in order to obtain a fair value for share options accounting, BSM model values need to be somehow corrected. The use of the BSM model as such leads to share options expenses too high compared to the arm's length prices. It shows that the standard BSM model does not represent either true or a fair view of the financial statement for company valuation Originality/ values - The price differential will offers a unique opportunity to compare the BSM model values with the market values of stock options and explain this price differential. By examining the validity of BSM formula to value ESOs, it will offer an opportunity for standard setters to define more accurately the values of ESOs to be included in the financial statements.